Pengaruh Penggunaan Gadget dan Self Regulated Learning terhadap Minat Belajar pada Mata Kuliah Web Design Mahasiswa Pendidikan Administrasi Perkantoran - Nadiya Rahmadina; Marsofiyati Marsofiyati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This study aims to investigate the influence of gadget use and self-regulated learning on the learning interest of students majoring in Office Administration Education who take Web Design courses. Through a quantitative approach, data was collected from odd semester students in the 2023/2024 academic year using a validated questionnaire. The results of multiple linear regression analysis show that gadget use and self-regulated learning significantly affect learning interest, with a coefficient of determination (R²) of 0.65, which means 65% of the variation in learning interest can be explained by these two variables. Hypothesis testing showed an F-statistic value of 24.56 (df = 2, sig < 0.01), confirming a significant influence between the independent variables and study interest. The results of this study indicate that gadget usage and self-regulated learning have a significant positive influence on the learning interest of students majoring in office administration majoring in web design.